REDESAIN TAS UNTUK JASA POTONG RAMBUT PANGGILAN - Kevin Aryola Wardhana; Choirul Anam (Institut Teknologi Adhi Tama Surabaya, 2022)
As time goes by, now we can order all forms of services online, one of which is a call barber service, this service arose because of the need for some people to do hair care. Some people need this service because not everyone has free time to go to the barbershop due to busy activities, a person who is very sick to the elderly also requires on-call barbershop services due to mobility problems. This gave rise to a bag model that aims to make it easier to carry the equipment that will be carried by the barber, but most barbers make this bag themselves by modifying a small suitcase by providing a bulkhead but there is no special placement for the equipment used. The design of this product will be a solution to the problems of today's on-call barbers. The design process uses a mix method, namely qualitative and quantitative research methods. then used work requirements analysis, shape analysis, dimensional analysis, material analysis, systems analysis, color analysis, analysis of techniques using laser cutting, and ergonomics analysis. Then we get a design synthesis, design concept, and initial sketch which is then closed with conclusions and suggestions. The design of this product carries an iconic concept, because the design of the bag that will be made later will be made as iconic as possible to display a bag with a design that uses the colors on the barbershop symbol.